2002
DOI: 10.1093/jn/132.6.1258
|View full text |Cite
|
Sign up to set email alerts
|

Lactating Sows and Suckling Piglets Preferentially Incorporate RRR- over All-rac-α-Tocopherol into Milk, Plasma and Tissues

Abstract: Synthetic vitamin E, all-rac-alpha-tocopherol, contains eight different stereoisomers, only one of which, RRR-alpha-tocopherol, occurs naturally. The objective of this investigation was to evaluate the relative abilities of these two vitamin E forms to enrich piglet tissues when fed as alpha-tocopheryl acetates to sows during pregnancy and lactation. alpha-Tocopherol delivery to fetuses and to suckling piglets was monitored by feeding 150 mg each of d(3)-RRR-alpha- and d(6)-all-rac-alpha-tocopheryl acetate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
57
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 32 publications
13
57
0
1
Order By: Relevance
“…This has been widely reported in the literature and is attributed to increased stress (Lauridsen et al, 2002;Moreira and Mahan, 2002;Wilburn et al, 2008). However, it is interesting to note that the magnitude of the decrease was greatest in groups with higher serum concentrations of α-tocopherol at weaning (P < 0.001, interaction time × treatment; Table 3).…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…This has been widely reported in the literature and is attributed to increased stress (Lauridsen et al, 2002;Moreira and Mahan, 2002;Wilburn et al, 2008). However, it is interesting to note that the magnitude of the decrease was greatest in groups with higher serum concentrations of α-tocopherol at weaning (P < 0.001, interaction time × treatment; Table 3).…”
Section: Resultssupporting
confidence: 60%
“…Those piglets from sows supplemented with the natural source of vitamin E (1/2-NAT-1/2-NAT; 1/2-NAT-15-SINT; 1/3-NAT-1/3-NAT; 1/3-NAT-15-SINT) had higher RRR (P < 0.001) and lower RRS (P < 0.001), RSS (P < 0.001) and RSR (P < 0.001) α-tocopherol stereoisomers proportions at day 39 of age than those from sows supplemented with the synthetic form (30-SINT-1/2-NAT; 30-SINT-1/3-NAT; 30-SINT-15-SINT). Lauridsen et al (2002) previously reported that lactating sows and suckling piglets preferentially incorporate RRRover all-rac-α-tocopherol into milk, plasma and tissues. Hoppe and Krennrich (2000) and Stone et al (2003) found similar results in humans.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations